Age group differences in psychological distress and leisure-time exercise/socioeconomic status during the COVID-19 pandemic: a cross-sectional analysis during 2020 to 2021 of a cohort study in Japan - Saito, Yoshinobu; Nakamura, Sho; Watanabe, Kaname; Ikegami, Hiromi; Shinmura, Naoko; Sato, Shinya; Miyagi, Yohei; Narimatsu, Hiroto (Frontiers in Public Health, 2023)
Objective: This study aimed to determine the association between psychological distress and leisure-time exercise/socioeconomic status by age group, using data from a cohort study in Japan during the COVID-19 pandemic. Methods: This cross-sectional study was conducted among participants in the ME-BYO cohort, aged 20–85 years, living or working in Kanagawa, Japan. A questionnaire was disseminated to 1,573 participants (51.7% men) between December 2020 and March 2021. The questionnaire items included psychological distress (using the 6-item Kessler Psychological Distress Scale [K6]), leisure-time exercise, and socioeconomic status. Multivariate analyses were conducted using logistic regression analysis for each age group. Results: We found that 47.4% of 20–39-year-olds, 40.6% of 40–64-year-olds, and 28.3% of 65–85-year-olds experienced psychological distress (K6: ≥5 points). For those aged 20–39 years, leisure-time exercise (odds ratio [OR] (95% confidence interval) = 0.45 (0.28–0.73)] and higher annual household income [0.53 (0.32–0.90)] were associated with less psychological distress. For those aged 40–64 years, older age was associated with less psychological distress, while full-time work [1.98 (1.05–9.71)] was associated with more psychological distress. In the 65–85-year age group, higher education and higher annual income tended to be associated with less psychological distress. For those over 40 years of age, living with other(s) was associated with reduced psychological distress. Conclusion: In the general population of Japan, not engaging in leisure-time exercise and low income affect psychological distress among young adults. Further detailed studies are needed to consider overall physical activity, job type, and work style.